Digital transformation and economic growth – DESI improvement and implementation - Olczyk, Magdalena; Kuc-Czarnecka, Marta (Technological and Economic Development of Economy, 2022)
The paper aims to improve the methodology of the Digital Economic and Society Index (DESI), the European Commission’s newest index to assess the development of the digital economy. In particular, we investigate whether methodological changes to the structure of DESI improve its ability to capture the digital transformation of EU economies. Using the sensitivitybased analysis, we check whether the selection of weights of individual elements included in the DESI is optimal or should be improved. We also verify the importance of DESI in explaining changes in GDP per capita in EU economies. In the literature, we find that digital transformation has enabled the creation of new business models and maximized efficiency in traditional firms. Using DESI, we empirically test whether the gap between rich and poor countries in European Union can be closed or eliminated through rapid and intensive digital transformation. Our results show that the DESI – when modified by eliminating the pillars on internet services and digital public services – has the same explanatory power. Connectivity is the dimension with the largest impact on digital transformation in EU countries. We also find that DESI is a significant regressor to explain changes in GDP per capita in EU countries.